Overview on the use of probiotic in the treatment of atopic dermatitis : Gambaran umum tentang penggunaan probiotik dalam pengobatan dermatitis atopik - AL-Saraj, Ruaa N.; AL-Ashou, Safa M.; Bader, Shahad A. (Indonesian Journal on Health Science and Medicine, 2025)
Atopic dermatitis is a condition that reduces the quality of life for those afflicted. This syndrome is often linked to recurrent dermatological infections, heightened allergic sensitivity, and compromised skin barrier integrity. The prevalence of atopic dermatitis ranges from 1% to 20%. Research on probiotics has progressed markedly, showing effectiveness in addressing several conditions, including atopic dermatitis. A multitude of research investigates their effectiveness in treating and easing the symptoms of atopic dermatitis.This review will analyse the importance of probiotics in the management of atopic dermatitis, the possible mechanisms involved, and recent research on the subject. Highlights: Immune Modulation. Probiotics help balance Th1/Th2 responses and promote regulatory T cells to reduce allergic reactions and inflammation. Clinical Evidence. Multiple studies and meta-analyses support probiotics' efficacy in reducing SCORAD scores and AD severity. Strain-Specific Benefits. Lactobacillus and Bifidobacterium strains show most effectiveness, especially in mixed formulations over monotherapy. Keywords: Probiotics, Atopic Dermatitis, Inflammation, Allergy, Immune Response